ทฤษฎีสะกิดกับผลลัพธ์ผู้เรียนตามมาตรฐานการศึกษาของชาติ - ปั้นพงษ์ กอบกาญจน์; เต็งสุวรรณ์ ปาริฉัตร (วารสารสันติศึกษาปริทรรศน์ มจร, 2021)
Nudge theory can be applied to motivate the target group to change its behavior without compulsion, which is widely applied in health and finance aspects. However, there are only a small number of academic papers that use nudge theory in education. This article aims to study the principles of nudge theory based on behavioral economics approach and to suggest guidelines for applying the nudge theory in formulating policy for curricula and instructional management of educational institutions. A review of the literature, theories and research related to the use of nudge theory in various policy contexts were analyzed to determine the desired outcomes according to national educational standards. The results showed that the “Nudge Theory” could be used to design educational activities to promote desirable behaviors from early childhood to higher education levels. It can be applied through four principles: (1) Make It Easy (2) Make It Attractive (3) Make It Social and (4) Make It Timely, as a guideline for encouraging behavior that meets educational standards. Of course, if educators can understand, appreciate, and design decision-making options that can generate desirable outcomes, this will lead to more efficient development of the country’s education system.